Does the Social Capital Matters in Buyer-Supplier Relationships? A Thai Perspective - Wallop Piriyawatthana; Tawat Phumdara; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2020)
The main objective of the current study is to investigate the influence of the social capital theory in the relationship between buyer and supplier relationship. The study is of the view that the there are certain managerial implications of social capital in terms of buyer supplier relationships, therefore, considering these, significant resources are invested by the buyers to generate social capital along with its suppliers. Thus, a social capital which is earned after huge efforts may sometimes result in poor decision making, opportunistic behaviors, and loss of objectivity. The study has used the survey-based methodology and examined the manners or the Thai Petro chemical firms Considering a buyer supplier relationship, we attempt to theorize social capital contradiction and empirical evidence is presented for the social capital and performance relationship as a curvilinear relationship at inter-firm level. The results of this research are found to be in line with a few recent researches which examined the impact of this curvilinear relationship at group, network, or individual level. The findings suggest that social capital and performance relationship has an inverted curvilinear relationship. The empirical findings indicate that in case of buyer-supplier collaboration for gaining strategic benefits, more time is consumed for making it to the threshold level, as compared to the case of operational benefits.